First report on the molecular detection, phylogeny, virological and pathological investigations of Avibacterium paragallinarum in chickens in Turkey - Umar, Sajid; Ongor, Hasan; Bayraktar, Erhan; Gurgen, Hazal Ozturk; Sigirci, Belgi Diren; Satir, Esra; Yilmaz, Huseyin (Polish Soc Veterinary Sciences Editorial Office, 2020)
Avibacterium paragallinarum is an important pathogen affecting the respiratory tract of chickens. There is a paucity of information on the molecular characteristics and pathology of A. paragallinarum in Turkish poultry flocks. In the present study, broiler and layer flocks (n = 2) suspected of viral infections with serious respiratory signs and significant mortality were visited. Chickens showed various disease signs and necropsy lesions, including purulent nasal discharge, respiratory distress, facial edema, sticky eyes, mucoid tracheitis, hemorrhagic inflammation of the infraorbital sinuses along with fibrinous mass and conjunctivitis. Histopathological lesions included loss of cilia along with necrosis and exfoliation of the superficial mucosal epithelium of the trachea, facial cellulitis, dermatitis, fibrinous plasmatic edema and infiltration of inflammatory cells, especially heterophils. A. paragallinarum was detected in tissue samples by species-specific polymerase chain reaction (PCR). The sequencing and phylogenetic analysis of the core region of the hemagglutinin (HA) gene revealed that Turkish strains detected here belonged to serotype A (serovar A1). They were related to strains reported from India (VRDC), the United States (0083), and Japan (0221), which are representatives of serovar A1. A homology of 88-90% was found between Indian strains and the Turkish strains detected in this study. Surprisingly, only vaccine strains of infectious bronchitis virus (IBV) were detected as a co-infecting agent in all samples positive for A. paragallinarum. Our findings suggest that A. paragallinarum may be an emerging pathogen in Turkish poultry flocks, and direct PCR may facilitate rapid diagnosis of infectious coryza. These results will also help to develop control strategies for A. paragallinarum.
Keywords: Avibacterium paragallinarum; chicken; PCR; histopathology; phylogenetic analysis; Turkey